Production of recombinant EMA-1 protein and its application for the diagnosis of Theileria equi using an enzyme immunoassay in horses from São Paulo State, Brazil - Baldani, Cristiane Divan; Hilario, Eduardo; Nakaghi, Andréa Cristina Higa [UNESP]; Bertolini, Maria Célia [UNESP]; Machado, Rosangela Zacarias [UNESP] (FapUNIFESP (SciELO), 2011)
The erythrocytic-stage surface protein, Equi Merozoite Antigen 1 (EMA-1), is a major candidate for the development of a diagnostic antigen for equine piroplasmosis. In order to establish an effective diagnostic method for practical use, the gene encoding the entire EMA-1 of Theileria equi Jaboticabal strain was cloned and expressed in scherichia coli as a histidine-tagged protein (His6-EMA1). The expressed EMA-1 reacted with specific antibodies in Western blot and had an apparent molecular mass of 34 kDa which was largely consistent with its theoretical value. The nucleotide sequence of the EMA-1 gene of Jaboticabal strain was comparatively analyzed with other published sequences. The results indicated a high degree of homology with EMA-1 genes of all other strains isolated from various countries. The recombinant purified His6-EMA1 protein was tested in an enzyme-linked immunosorbent assay (ELISA) for the detection of antibodies anti-T. equi in horses. The ELISA clearly differentiated T. equi-infected from Babesia caballi-infected horse sera or normal horse sera. Field serum samples collected from horses in the State of São Paulo, Southeastern Brazil, were examined for the diagnosis of T. equi infection by ELISA. Of 170 samples analyzed, 95.88% (163/170) were positive for T. equi infection. These results suggest that the His6-EMA1 protein expressed in E. coli could be a reliable immunodiagnostic antigen for ELISA test and that T. equi infection is a serious concern in the State of São Paulo, Brazil.
Produção da proteína recombinante EMA-1 e sua aplicação para o diagnóstico baseado no imunoensaio enzimático de Theileria equi em equinos do Estado de São Paulo, Brasil
Keywords: Diagnosis; ELISA; EMA-1; Theileria equi